NILAI PENDIDIKAN KARAKTER PADA ANIMASI “NUSSA” (KAJIAN SEMIOTIK SAUSSURE) - Tita Tita Tita; Syihabuddin Syihabuddin (STKIP PGRI SUMENEP, 2023)
This study aims to find out and describe the value of character education in the film